2020
DOI: 10.1101/2020.10.14.339192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterozygous deletion of SYNGAP enzymatic domains in rats causes selective learning, social and seizure phenotypes

Abstract: Pathogenic variants in SYNGAP1 are one of the most common genetic causes of nonsyndromic intellectual disability (ID) and are considered a risk for autism spectrum disorder (ASD). SYNGAP1 encodes a synaptic GTPase activating protein that modulates the intrinsic GTPase activity of several small G-proteins and is implicated in regulating the composition of the postsynaptic density. By targeting the deletion of exons encoding the calcium/lipid binding (C2) and GTPase activating protein (GAP) domains, we generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…1A, Supplementary Fig. 1) recordings when animals were in a quiet-wake state 17 . To determine whether Syngap +/ Δ-GAP animals have abnormalities in their brain state distribution, we classified all individual 5 s recording epochs from those previous recordings as NREM sleep, REM sleep or wake (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A, Supplementary Fig. 1) recordings when animals were in a quiet-wake state 17 . To determine whether Syngap +/ Δ-GAP animals have abnormalities in their brain state distribution, we classified all individual 5 s recording epochs from those previous recordings as NREM sleep, REM sleep or wake (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties in both initiating and maintaining sleep as well as reduced overall sleep duration have been reported in individuals with SYNGAP1 mutations 3,8,9 . In our previous work we performed 6 hr recordings EEG recordings and found that Syngap +/ Δ-GAP animals displayed absence seizures at a higher rate than controls 17 . We have further analysed these recordings, which were made during daylight hours, resulting in rats spending approximately half of the recording time asleep.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations